تنمية مهارات الدعوة عبر مواقع التواصل الاجتماعي لدى طالبات قسم الدراسات الإسلامية - المطيري، حنان بنت منير بن غبيش (جامعة الامام محمد بن سعود الإسلامية - الجمعية السعودية للدراسات الدعوية, 2018)
يهدف البحث الحالي إلى تنمية مهارات الدعوة عبر مواقع التواصل الاجتماعي لدى طالبات قسم الدراسات الإسلامية، واستخدمت الدراسة: المنهج شبه التجريبي؛ حيث تكون مجتمع الدراسة من جميع طالبات قسم الدراسات الإسلامية بكلية العلـوم والدراسات الإنسانية برماح، جامعة المجمعة بالمملكة العربية السعودية، وبلغ حجم عينة الدراسة (30) طالبة من طالبات قسم الدراسات الإنسانية برماح؛ تم اختيارهم بطريقة عشوائية، ولتحقيق أهداف الدراسة؛ قامت الباحثة بإعداد استبانة لجمع المعلومات، وقد أظهرت نتائج الدراسة: وجود فروق ذات دلالة إحصائية في مهارات الدعوة (التخطيط، التنفيذ، التفاعل) بين متوسطي درجات عينة الدراسة في القياس القبلي والبعدي لاستبيان مهارات الدعوة لصالح التطبيق البعدي.
The present research aims to develop the skills of Claim of affinity through the social media for female students of the Department of Islamic Studies; the study used semi- experimental method. Where the society of the study consisted of all students of the Department of Islamic Studies at Faculty of Science and Humanities Studies at Barmah - University of Majma - Saudi Arabia, The sample size of the study was (30) female students of the Department of Humanities studies selected randomly. To achieve the objectives of the study, the researcher prepared a questionnaire to gather information. The results of the study showed that there were statistically significant differences in the skills of Claim of affinity (planning, implementation, interaction) between the average scores of the sample of the study in the pre-measurement and post measurement of Claim of affinity silks questionnaire for the post-application.
Keywords: طلبة الجامعات -- الدعوة الإسلامية -- مواقع التواصل الاجتماعي -- مهارات الدعوة